Conventional or Atypical: FDI in the Internationalisation Process of Polish Firms - Trąpczyński, Piotr (Theory, Methodology, Practice – Review of Business and Management, 2014)
The principal aim of this study is to provide preliminary evidence on whether Polish firms behave according to the conventional theory of firm internationalisation. To fulfil this objective, an overarching research hypothesis that Polish firms follow gradual expansion patterns is formulated based on theoretical concepts and available data on Polish internationalisation. It is subsequently tested on a sample of 98 Polish outward investors. While the study confirms the gradual expansion patterns of Polish firms, in which exports and contract manufacturing mostly precede foreign direct investiment (FDI) projects in a given host country, there is also visible evidence for irregular internationalisation paths, in which FDI is the first entry mode into foreign markets. The vast majority of Polish outward investors still control a limited network of foreign subsidiaries. The paper is one of the few studies explicitly related to establishment chains of Polish firms, thus providing an empirical contribution to the debate on the internationalisation of emerging multinationals. The limited scope of Polish firms' internationalisation indicates an important need for a more widespread implementation of support policies.